Comparison Of Amount Of Elastin Fibres With Histopathological Parameters And Elastography In Breast Carcinoma - Utnal, Preeti Ashok; A, Hemalatha; Sakalecha, Anil Kumar; BH, Parameshwar Keerthi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Breast carcinoma is the most freÂquently diagnosed cancer and the chief cause of cancer deaths among women worldwide. Cancer registry data shows that incidence of carcinoma breast ranges from 19.3 to 89.7 per 100,000 population (India) and a total of 27.5% cases of cancers in Karnataka. The normal breast tissue is comprised of two major compartments, the epithelium and the stroma. Normally elastic tissue can be seen in periductal and perivascular region of breast. Elastosis, characterized by deposition of elastic fibers in the stroma of infiltrating ductal carcinoma was first described by Cheatle and Cutler, but extensively studied by Shivas & Douglas and others. Several methods for visual grading of elastosis have been proposed but all are semi quantitative and subjective and are dependent on the experience of the observed. Methods: Blocks of all 87 cases were retrieved from the histopathological section, department of Pathology of our institute. Data regarding the demographic details, clinical presentation of the cases are obtained from the medical record section of our medical record section of our college. The slides were stained with Verhoeffâ€™s van Gieson stain and were screened by two pathologists. Result: Out of 87 cases studied only 1 case showed elastin fibers score 0, 18 cases showed score 1, 46 cases showed score 2 and 22 cases showed score 3. There was statistical significant correlation between Tumor stage and amount of paratumoral elastin fibers. There was no statistical correlation between Tumor grade, Tumor size, Nodes, Nottingham prognostic index and Modified tsukba scoring and paratumoral elastosis. Out of 87 cases the ER IHC was done in only 23 cases out of which 10 cases showed positivity on Allred scoring and 13 cases were negative. For Progesterone receptors out of 23 cases 9 cases were positive on Allred scoring and 14 were negative and hence the correlation could not be done. The HER2neu was done in 23 cases out of 87 cases where the positivity was seen in 07 cases and it was equivocal in 03 cases and negative in 13 cases. Conclusion: Our results strongly indicate the presence of Peritumoral elastosis and the lower tumor grade. The paratumoral elastosis and lower tumor stage. Whether and how elastosis is mechanically involved in tumor development and progress requires further study.